2019
DOI: 10.33713/egetbd.463608
|View full text |Cite
|
Sign up to set email alerts
|

Geriatrik Olgularda Kronik Hastalıkların ve Polifarmasinin Ölüm Kaygısı ve Anksiyete Üzerine Etkisi

Abstract: ilaç kullanmayan geriatrik bireylerin ÖKÖ ve GAÖ puanlarından daha yüksek düzeyde bulundu (sırasıyla p değerleri: p=0.021, p=0.017). Ayrıca kronik hastalığı olan ve sürekli ilaç kullanan geriatrik bireylerde kronik hastalık sayısı ve kullanılan ilaç sayısı ile ÖKÖ ve GAÖ puanları arasında doğrusal bir ilişki bulunmuştur (sırasıyla r = 0.87, r = 0.81). SONUÇ: Bu çalışmada kronik hastalık varlığı ve çoklu ilaç kullanımı yaşlı olgularda anksiyete ve ölüm kaygısını arttıran etkenler olarak göze çarpmaktadır. Ayrı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…Higgins et al (2021), in their study, found that 87.4% of the participants in the study had a chronic disease and those with chronic diseases had a high level of anxiety to catch COVID-19. Karahan and Hamarta (2019) revealed that those with at least 3 chronic diseases had high levels of anxiety. Kasar et al (2016), according to the results of their study, predicted that the presence of chronic diseases in the participants will not always increase the level of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Higgins et al (2021), in their study, found that 87.4% of the participants in the study had a chronic disease and those with chronic diseases had a high level of anxiety to catch COVID-19. Karahan and Hamarta (2019) revealed that those with at least 3 chronic diseases had high levels of anxiety. Kasar et al (2016), according to the results of their study, predicted that the presence of chronic diseases in the participants will not always increase the level of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, the population over the age of 65 has increased by 16% between 2014 and 2018, from 6,192,962 people to 7,186,204 people, and the ratio of the elderly population to the general population is 8.3%. This figure is estimated to reach 10% by 2025 1 .…”
Section: Introductionmentioning
confidence: 98%
“…The number of the elderly population is increasing year by year in both developed and developing countries due to the increase in the world population and developments in the diagnosis and treatment of chronic health problems. The number of people over the age of 65 in the world is estimated to increase to 1.5 billion by 2050 [1,2]. In Turkey, the population over the age of 65 has increased by 16% between 2014 and 2018, from 6,192,962 people to 7,186,204 people, and the ratio of the elderly population to the general population is 8.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Yaşlılık döneminde ortaya çıkan birçok değişiklik ve kronik hastalıklar, fizik gücün azalması nedeni ile birey kendini ölüme daha yakın hissetmektedir (Üstüner Top, Saraç ve Yaşar, 2010). Karahan ve Hamarta (2019) kronik hastalığı olan yaşlılarda ölüm kaygısının daha yüksek olduğunu tespit etmiştir. Ölüm kaygısı, birey ölüm tehdidi altında olduğunda tetiklenebilecek bir savunma mekanizmasından kaynaklanan bilinçli veya bilinçsiz bir psikolojik durum olup bireyin artık var olmayacağının, kendisini ve dünyayı kaybedebileceğinin, bir hiç olabileceğinin farkındalığı sonrası gelişir (Üstüner Top vd., 2010;Zhang, Peng, Gao, Huang, Cao, Zheng ve Miao, 2019).…”
Section: Introductionunclassified